Experimental habitat fragmentation increases linkage disequilibrium but does not affect genetic diversity or population structure in the Amazonian liverwort Radula flaccida - Zartman, Charles Eugene; McDaniel, Stuart F.; Shaw, A. Jonathan (Molecular Ecology, 2006)
Habitat fragmentation increases the migration distances among remnant populations, and is predicted to play a significant role in altering both demographic and genetic processes. Nevertheless, few studies have evaluated the genetic consequences of habitat fragmentation in light of information about population dynamics in the same set of organisms. In a 10 000-km2 experimentally fragmented landscape of rainforest reserves in central Amazonia, we examine patterns of genetic variation (amplified fragment length polymorphisms, AFLPs) in the epiphyllous (e.g. leaf-inhabiting) liverwort Radula flaccida Gott. Previous demographic work indicates that colonization rates in this species are significantly reduced in small forest reserves. We scored 113 polymorphic loci in 86 individuals representing five fragmented and five experimentally unmanipulated populations. Most of the variation (82%) in all populations was harboured at the smallest (400 m2) sampling unit. The mean (± SD) within-population genetic diversity (Nei's), of forest remnants (0.412 ± 0.2) was indistinguishable from continuous (0.413 ± 0.2) forests. Similarly, FST was identical among small (1- and 10-ha) and large (≥ 100-ha) reserves (0.19 and 0.18, respectively), but linkage disequilibrium between pairs of loci was significantly elevated in fragmented populations relative to those in continuous forests. These results illustrate that inferences regarding the long-term viability of fragmented populations based on neutral marker data alone must be viewed with caution, and underscore the importance of jointly evaluating information on both genetic structure and demography. Second, multilocus analyses may be more sensitive to the effects of fragmentation in the short term, although the effects of increasing linkage disequilibrium on population viability remain uncertain. © 2006 The Authors.
Keywords: Environment; Gene Expression Regulation; Gene Linkage Disequilibrium; Genetic Variability; Genetics; Liverwort; Physiology; Plant Leaf; Tropic Climate; Environment; Gene Expression Regulation, Plant; Hepatophyta; Linkage Disequilibrium; Plant Leaves; Tropical Climate; Variation (genetics); Radula Flaccida